Overexpression of Arabidopsis Nucleotide-Binding and Leucine-Rich Repeat Genes RPS2 and RPM1(D505V) Confers Broad-Spectrum Disease Resistance in Rice - Li, Zhaowu; Huang, Jianzhong; Wang, Zhangying; Meng, Fen; Zhang, Siyuan; Wu, Xiaoqiu; Zhang, Zhihong; Gao, Zhiyong (Frontiers in Plant Science, 2019)
The nucleotide-binding domain leucine-rich repeat (NLR) immune receptors play important roles in innate plant immunity. The activation of NLRs is specifically induced by their cognate effectors released from pathogens. Autoactive NLRs are expected to confer broad-spectrum resistance because they do not need cognate effectors to activate their immune responses. In this study, we demonstrated that the NLR genes RPS2 and RPM1(D505V) from Arabidopsis were autoactive in Oryza sativa and conferred broad-spectrum resistance to fungal pathogen Magnaporthe oryzae, bacterial pathogen Xanthomonas oryzae pv. oryzae (Xoo), and pest brown planthopper (BPH, Nilaparvata lugens Stål). These results revealed that interfamily transfer of dicot NLRs to monocot species could be functional. The transgenic plants displayed early and strong induction of reactive oxygen species (ROS), callose deposition, and expression of defense-related genes after challenged with M. oryzae. The transcriptome analysis showed that the expressions of some defense-related genes were primed to adapt the transformed autoactive NLRs in the transgenic plants. This study indicates that autoactive NLRs are a promising resource for breeding crops with broad-spectrum resistance and provides new insights for engineering disease resistance.